Modulation of Gilthead Sea Bream Gut Microbiota by a Bioactive Egg White Hydrolysate: Interactions Between Bacteria and Host Lipid Metabolism - Naya-Català, Fernando; Wiggers, Giulia A.; Piazzon, M. Carla; López-Martínez, Manuel I.; Estensoro, Itziar; Calduch-Giner, Josep A.; Martínez-Cuesta, M. Carmen; Requena, Teresa; Sitjà-Bobadilla, Ariadna; Miguel, Marta; Pérez-Sánchez, Jaume (Frontiers in Marine Science, 2021)
This study aimed to highlight the relationship between diet, animal performance and mucosal adherent gut microbiota (anterior intestine) in fish fed plant-based diets supplemented with an egg white hydrolysate (EWH) with antioxidant and anti-obesogenic activity in obese rats. The feeding trial with juveniles of gilthead sea bream (Sparus aurata) lasted 8 weeks. Fish were fed near to visual satiety with a fish meal (FM)/fish oil (FO) based diet (CTRL) or a plant-based diet with/without EWH supplementation. Specific growth rate decreased gradually from 2.16% in CTRL fish to 1.88% in EWH fish due to a reduced feed intake, and a slight impairment of feed conversion ratio. Plant-based diets feeding triggered a hyperplasic inflammation of the anterior intestine regardless of EWH supplementation. However, EWH ameliorated the goblet cell depletion, and the hepatic and intestinal lipid accumulation induced by FM/FO replacement. Illumina sequencing of gut mucosal microbiota yielded a mean of 136,252 reads per sample assigned to 2,117 OTUs at 97% identity threshold. The bacterial diversity was similar in all groups, but a significantly lower richness was found in EWH fish. At the phylum level, Proteobacteria reached the highest proportion in CTRL and EWH fish, whereas Firmicutes were decreased and Actinobacteria increased with the FM/FO replacement. The proportion of Actinobacteria was restored by dietary EWH supplementation, which also triggered a highest amount of Bacteroidetes and Spirochaetes. At a closer look, a widespread presence of Lactobacillales among groups was found. Otherwise, polysaccharide hydrolases secretors represented by Corynebacterium and Nocardioides were increased by the FM/FO replacement, whereas the mucin-degrading Streptococcus was only raised in fish fed the plant-based diet without EWH. In addition, in EWH fish, a higher abundance of Propionibacterium was related to an increased concentration of intestinal propionate. The antagonism of gut health-promoting propionate with cholesterol could explain the inferred underrepresentation of primary bile acid biosynthesis and steroid degradation pathways in the EWH fish microbiota. Altogether, these results reinforce the central role of gut microbiota in the regulation of host metabolism and lipid metabolism in particular, suggesting a role of the bioactive EWH peptides as an anti-obesity and/or satiety factor in fish.